Humanitarian intervention in Iraq, a legal study (Numerus academy review, 2026)
humanitarian intervention does not threaten the political or regional independenceof any State or violate its sovereignty because the goal is different from this, it aims to protect human rights and to stop humanitarian abuses, but nonetheless surely there will be some effects and complications on the sovereignty of the intervener states where a human in any way special intervention military. Iraq is the best arena for confrontation betweenhumanitarian intervention and national sovereignty through military interventionfollowing the decision 688, which was a new precedent in the international arena.